Effects of Replacing Alfalfa Hay With Native Grass Hay in Pelleted Total Mixed Ration on Physicochemical Parameters, Fatty Acid Profile, and Rumen Microbiota in Lamb - Du, Shuai; You, Sihan; Sun, Lin; Wang, Xiaolong; Jia, Yushan; Zhou, Yulei (Frontiers in Microbiology, 2022)
This study aimed to investigate the effects of replacing alfalfa with native grass on growth performance, meat quality and rumen microbiota of lambs. Forty-five six-month-old Ujimqin lambs, with a live bodyweight of 29.50±0.26 kg were used for the experiment and the lambs were to 3 diet treatments (5 lambs per pen) with 30 square meters per pen in semi-open housing based on similar BW. The lambs have received 30% alfalfa (HA, high alfalfa percentage group), 20% alfalfa (MA, moderate alfalfa percentage group) and 10% alfalfa (LA, low alfalfa percentage group) diets, respectively (dry matter basis). The diet treatments had a significant (P < 0.05) influence on the dry matter intake of lambs and the dry matter intake increased with the increasing of the percentages of native grass hay, while the significantly (P < 0.05) lower final bodyweight and average daily gain were observed in the MA and LA groups compared to that in the HA group. The diet had a significant (P < 0.05) difference in meat pH value, water loss rate, cooked meat rate, moisture and intramuscular fat, while no significant (P > 0.05) difference was found on protein. As native grass hay percentages increased in the diet, the content of palmitic and palmitoleic in the HA and MA groups were significantly (P < 0.05) lower than that in the LA groups, compared to the HA group, the content of elaidic, oleic and linoleic were significantly (P < 0.05) increased in the MA and LA groups. The content of α-linolenic was significantly (P < 0.05) higher in the LA group than that in the HA and MA groups. The principal coordinates analysis profile displayed that the composition of the bacterial community of these groups was distinctly separated from each other. No significant (P > 0.05) difference was observed on the dominant rumen bacteria at the phyla and genus levels. In summary, these findings could provide knowledge of how the diet affects the animal performance, meat quality of lambs and microbiota of the rumen, lay a theoretical basis for replacing alfalfa with native grass.